Developing Sigil-Based Nahwu E-Module: Bridging Classical Arabic Grammar and Digital Pedagogy in Islamic Higher Education: Pengembangan E-Modul Nahwu Berbasis Sigil: Menjembatani Tata Bahasa Arab Klasik dan Pedagogi Digital di Pendidikan Tinggi Islam - Niswatush Sholihah; Muhammad Mas'ud; Dhea Isfa’atin; Burhan Yusuf Habibi (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2025)
Technological advancements necessitate that educators develop electronic teaching materials to help students grasp complex Nahwu concepts. In Islamic religious contexts, Nahwu plays a fundamental and strategic role in understanding religious texts. This study aims to develop a Sigil-based Nahwu e-module and analyze its effectiveness in instruction. The research employs the Borg & Gall R&D model, with stages encompassing data collection, planning, product development, validation, and field testing. Data were gathered through observation, interviews, documentation, questionnaires, and tests. The e-module’s feasibility, validated by design and content experts, met “very feasible” criteria. Small-group trials yielded a 93.1% score (excellent), and large-group trials achieved 91% (excellent). Learning mastery rates rose from 45.45% (pre-test) to 90.90% (post-test). Thus, the Nahwu e-module positively influences students’ learning processes. It enhances learning autonomy, interactivity, engagement, academic digital literacy, and material standardization. Additionally, this research strengthens competence in interpreting religious texts, underscores Arabic linguistics as foundational, not merely theoretical, for accurate Islamic understanding, and advances Islamic values through technology.